The utility of upper limb loading device in determining optimal walking ability in ambulatory individuals with spinal cord injury - Makamas Kumprou; Pipatana Amatachaya; Thanat Sooknuan; Preeda Arayawichanon; Thiwabhorn Thaweewannakij; Sugalya Amatachaya (World Scientific Publishing, 2021)
Background: Walking devices are frequently prescribed for many individuals, including those with spinal cord injury (SCI), to promote their independence. However, without proper screening and follow-up care, the individuals may continue using the same device when their conditions have progressed, that may possibly worsen their walking ability. Objective: This study developed an upper limb loading device (ULLD), and assessed the possibility of using the tool to determine the optimal walking ability of ambulatory participants with SCI who used a walking device daily (n=49). Methods: All participants were assessed for their optimal walking ability, i.e., the ability of walking with the least support device or no device as they could do safely and confidently. The participants were also assessed for their amount of weight-bearing on the upper limbs or upper limb loading while walking, amount of weight-bearing on the lower limbs or lower limb loading while stepping of the other leg, and walking performance. Results: The findings indicated that approximately one third of the participants (31%) could progress their walking ability from their current ability, whereby four participants could even walk without a walking device. The amount of upper limb loading while walking, lower limb loading ability, and walking performance were significantly different among the groups of optimal walking ability (p<0.05). Furthermore, the amount of upper limb loading showed negative correlation to the amount of lower limb loading and walking performance (ρ=−0.351 to −0.493, p<0.05). Conclusion: The findings suggest the potential benefit of using the upper limb loading device and the amount of upper limb loading for walking device prescription, and monitoring the change of walking ability among ambulatory individuals with SCI.